2020
DOI: 10.1038/s41467-020-18899-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tides and sea-level on deep-sea Arctic methane emissions

Abstract: Sub-sea Arctic methane and gas hydrate reservoirs are expected to be severely impacted by ocean temperature increase and sea-level rise. Our understanding of the gas emission phenomenon in the Arctic is however partial, especially in deep environments where the access is difficult and hydro-acoustic surveys are sporadic. Here, we report on the first continuous pore-pressure and temperature measurements over 4 days in shallow sediments along the west-Svalbard margin. Our data from sites where gas emissions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…Römer et al (2016) suggested that methane exsolution caused by tidal pressure variations in the Clayoquot Slope at 1,250 m may contribute to plume activation, but cannot explain the long duration increase in venting that were observed in response to hydrostatic pressure changes. Sultan et al (2020) found evidence that gas exsolution from pore fluids does occur during low tides, but that this is not sufficient alone to trigger the release of gas in the water column at Arctic seeps on the Vestnesa Ridge. Our results concur with this latter finding as we could not relate the reactivation of quiescent vents to a particular tidal phase.…”
Section: Tidal Modulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Römer et al (2016) suggested that methane exsolution caused by tidal pressure variations in the Clayoquot Slope at 1,250 m may contribute to plume activation, but cannot explain the long duration increase in venting that were observed in response to hydrostatic pressure changes. Sultan et al (2020) found evidence that gas exsolution from pore fluids does occur during low tides, but that this is not sufficient alone to trigger the release of gas in the water column at Arctic seeps on the Vestnesa Ridge. Our results concur with this latter finding as we could not relate the reactivation of quiescent vents to a particular tidal phase.…”
Section: Tidal Modulationmentioning
confidence: 99%
“…Decreased hydrostatic pressure during low tides facilitates the opening, or dilatation, of fractures and makes it easier for pore gas pressure (P g ) to overcome the total stress (σ), leading to rapid gas discharge (Leifer & Boles, 2005;Liu & Flemings, 2009;Scandella et al, 2011;Tryon et al, 1999Tryon et al, , 2002. Recently, in-situ pore pressure measurements in gas-rich sediments on the Vestnesa Ridge (NW Svalbard) at water depths ranging from 910 and 1,330 m confirmed that tidally driven fluctuations of hydrostatic pressure generate local pore pressure gradients, which facilitate the release of gas into the water column during decreasing tide (Sultan et al, 2020). These mechanisms are generally well-supported by our results because the frequent increase of gas emissions we observe during tidal unloading is compatible with a pressure control on active gas emissions.…”
Section: Tidal Modulationmentioning
confidence: 99%
See 3 more Smart Citations